(NsO^INENIQ(B: [(NsTIHOTWORENIQ(B];s [(NzAPISI W ALXBOMAH(B] /s (N~ASTX (B18s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B:s (NnAUKA(B,s, 1982)
(Nw (B18 (NTOM SOBRANIQ SO^INENIJ a(B.(Np(B. (N~EHOWA WO[LI STIHOTWORENIQ(B, (NzAPISI W ALXBOMAH(B, Dubia, (NGIMNAZI^ESKOE(B, (NKOLLEKTIWNOE(B, (NREDAKTIROWANNOE(B.s
rus
Keywords: (NsTIHOTWORENIQs; (NzAPISIs